THE EFFECT OF PRODUCT QUALITY, BRAND, AND PRICE ON CONSUMER PURCHASING DECISIONS AT PT. BUANA RANTAI BERKAT ABADI - Veronica; Dessy Haryanti; Falvian Wantara; Gilbert Stephenson; Paulus Rianto; Nurmaidah Ginting (Journal of Research in Business, Economics, and Education, 2020)
Researchers took the object of research at PT. Buana Rantai Berkat Abadi caused by a decrease in employee performance. Researchers conducted research at PT. Buana Rantai Berkat Abadi located at Jalan Glugur N0. 31-32. This research approach is quantitative research. Type of quantitative descriptive research. The nature of this research is explanatory descriptive research. The population in this study were all customers of PT. Buana Rantai Berkat Abadi is as many as 133 customers. For testing the validity and reliability used by researchers were 30 customers and for the sample test were 100 customers. Before the regression model obtained is used to test the hypothesis, the model is first tested classic assumptions. The analysis model used is multiple linear regression analysis model, the coefficient of determination of simultaneous testing (F-Test) and partially (t-Test) Research Results as well as conclusions. The conclusion of this study is the quality of products and brands have a positive and significant effect on Purchasing Decisions at PT. Buana Rantai Berkat Abadi but the price does not affect purchasing decisions at PT. Buana Rantai Berkat Abadi. Simultaneously product quality, price and brand influence on purchasing decisions at PT. Buana Rantai Berkat Abadi.